The importance of hydraulic groundwater theory in catchment hydrology: The legacy of Wilfried Brutsaert and Jean‐Yves Parlange. Issue 9 (4th September 2013) - Troch, Peter A.; Berne, Alexis; Bogaart, Patrick; Harman, Ciaran; Hilberts, Arno G. J.; Lyon, Steve W.; Paniconi, Claudio; Pauwels, Valentijn R. N.; Rupp, David E.; Selker, John S.; Teuling, Adriaan J.; Uijlenhoet, Remko; et al.
Key Points Brutsaert and Parlange made landmark contributions to groundwater theory Hydraulic groundwater theory is basis of applications in hydrology Applications from drought analysis to climate impact